2007
DOI: 10.1016/j.gca.2006.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Cation exchange reactions controlling desorption of 90Sr2+ from coarse-grained contaminated sediments at the Hanford site, Washington

Abstract: Nuclear waste that bore 90 Sr 2+ was accidentally leaked into the vadose zone at the Hanford site, and was immobilized at relatively shallow depths in sediments containing little apparent clay or silt-sized components. Sr 2+ , 90 Sr 2+ , Mg 2+ , and Ca 2+ was desorbed and total inorganic carbon concentration was monitored during the equilibration of this sediment with varying concentrations of Na + , Ca 2+ . A cation exchange model previously developed for similar sediments was applied to these results as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…The behaviour of Sr is characterised by reversible ion exchange which is similar to the behaviour of Sr-90 in radioactively contaminated sediments elsewhere [2]. The exchanger phase in the Dounreay Shore Formation is most probably corrensite (mixed-layer smectite-chlorite) present in the bulk rock matrix.…”
Section: Model Inputsupporting
confidence: 54%
“…The behaviour of Sr is characterised by reversible ion exchange which is similar to the behaviour of Sr-90 in radioactively contaminated sediments elsewhere [2]. The exchanger phase in the Dounreay Shore Formation is most probably corrensite (mixed-layer smectite-chlorite) present in the bulk rock matrix.…”
Section: Model Inputsupporting
confidence: 54%
“…In fact, acid extraction has been used to remove 90 Sr for measurement (McKinley et al 2007). Sorption coefficients have not been found in the literature for pH values as low as what was calculated for the assumed FRG canister waste chemistry, although experimental data do show a marked decrease in cesium and strontium sorption on clays at pH values between 2 and 3 (Papelis and Um 2003).…”
Section: Ion-exchange Reactionsmentioning
confidence: 99%
“…Selectivity coefficients were not directly measured for this study, but a number of other studies have been performed with Hanford sediments to determine selectivity coefficients for exchange reactions involving Sr 2+ and Cs + . For example, McKinley et al (2007) reported selectivity coefficients for exchange reactions involving Sr 2+ that were estimated by fitting experimental data (Lichtner and Zachara 2005). Zachara et al (2002) and Liu et al (2004) developed different models and associated parameters describing Cs + sorption in Hanford sediments.…”
Section: Ion-exchange Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural minerals that contain uranium include betafite C [Ca 0.92 U 1.08 (Ti 2 O 7 )], most likely from granitic clasts commonly found in Hanford Site sediments (15% to 35% [Zachara et al 2007] (Finch and Murakami 1999;Liu et al 2004). Uranium and plutonium enrichment processes at the Hanford Site have resulted in the release of 202,703 kg of uranium to the ground surface (Simpson et al 2006) in a variety of aqueous solutions (acidic, basic, with organic complexants [citrate, ethylenediaminetetraacetic acid]) and inorganic ligands (CO 3 , PO 4 ), which would influence the uranium migration behavior.…”
Section: Uranium Mobility In the Hanford Site Vadose Zonementioning
confidence: 99%